A COMPREHENSIVE REVIEW OF “AN ANALYTICAL STUDY OF CONSUMER PROTECTION ACT 2019 ON REDRESSAL OF CONSUMER GRIEVANCE”. (International Journal of Food and Nutritional Sciences, 2022)
This comprehensive review paper scrutinizes the original research titled "An Analytical Study of Consumer Protection Act 2019 on Redressal of Consumer Grievance; A Study of E-Commerce Segment." The original study probes the impact and effectiveness of India's Consumer Protection Act (CPA) 2019 in offering a robust dispute resolution mechanism in the fast-evolving e-commerce landscape. The review highlights the study's central findings, notably the CPA 2019's role in enhancing consumer awareness about their rights and fostering greater transparency and accountability in the e-commerce sector. However, it also draws attention to some shortcomings identified in the original research, including the Act's limited purview in dealing with cross-border e-commerce disputes and issues surrounding data privacy. In providing an analysis, the review finds the original research to be thorough and insightful but recommends further exploration of international legislation comparisons and stakeholder qualitative insights for a more holistic perspective. It suggests future research to emphasize potential legislative amendments and the development of an international framework for e-commerce consumer protection. The review takes into account what the original study found and stresses that lawmakers and e-commerce platforms need to think about the problems they found as they improve their methods. It also shows how important practises that focus on the customer are for improving the image and trustworthiness of e-commerce sites. In the end, this study shows how important it is for laws to keep changing to keep up with the constantly changing problems in e-commerce. It respects the original study's addition to this conversation and suggests that it be used as a starting point for future research into how well consumer protection rules work in a marketplace that is becoming more global and digital.